Charitable according to whom ? The clash between Quebec’s societal values and the law governing the registration of charities - Chan, Kathryn (Les Cahiers de droit, 2008)
In the course of considering the public’s views on the accommodation of cultural minorities in Quebec, the Bouchard-Taylor Commission has produced a valuable record of the views held by Quebec’s voluntary sector organizations, and the societal values that are important to Quebec. In particular, it has underlined Quebec’s strong commitment to three broad public objects — the advancement of the French language and Quebec culture, the encouragement of interculturalism, and the promotion of secularism — that are not recognized as charitable objects under the common law.The Bouchard-Taylor Commission has therefore provided a timely and relevant backdrop against which to consider the real-life implications of using the common law of charitable trusts to give meaning to the statutory concept of charity (bienfaisance) in Quebec. Based on her observations of the Commission experience, the author suggests that the disjuncture between the law demarcating Quebec’s charitable sector and the social context within which the sector operates has become significant enough to merit a reconsideration of this longstanding approach.